Evaluation of The “Jum’at Beriman” Program at SMAN 1 Kuala Pembuang Using The CIPP Model (Context, Input, Process, and Product) - Assafiri Assafiri; Chandra Anugrah Putra; Endang Sri Suyati (Journal of Social Research, 2026)
SMAN 1 Kuala Pembuang is a leading school with outstanding achievements in both academics and extracurricular activities. One of its most distinctive qualities is a strong religious programme, making it a highly sought-after public school in the community. The Friday Faith programme, which has been running for 20 years, has successfully created an Islamic atmosphere and cultivated good character within the school environment. This study aims to describe the implementation of the Friday Faith programme at SMAN 1 Kuala Pembuang using the CIPP evaluation model (Context, Input, Process, and Product). This evaluative research employs a qualitative descriptive method, with data collected from the Principal, former Principal, Religious Education teachers, subject teachers, guidance counsellors, Student Council, and students through interviews, observation, and documentation, and analysed using qualitative data analysis techniques. The findings show that the programme has a strong legal foundation, clear objectives aligned with school and student needs, and broad stakeholder involvement. Programme preparation, scheduling, teacher competence, and funding are adequate, though infrastructure and team quality require improvement. The implementation of timing, venue, and teacher supervision is effective; however, greater student participation and more varied activity formats are needed. The programme has successfully improved religious knowledge, positive behaviour, student achievement, school identity, and community interest in enrolling at SMAN 1 Kuala Pembuang. In conclusion, the Friday Faith programme deserves to be continued and replicated in other educational institutions.